Strangulated Richter's incisional hernia presenting as an abdominal mass with necrosis of the overlapping skin. A case report and review of the literature - Sahsamanis, Georgios (Clin Case Rep, 2017)
Although rare, clinicians must be alerted of Richter hernias in patients presenting with innocuous gastrointestinal obstruction symptoms, synchronous with an erythematous hernia. An incarcerated incisional hernia located in a previous laparoscopic insertion site further raises suspicion, while timely surgical management is essential to avoid bowel perforation or resection.